2010
DOI: 10.1027/1864-9335/a000008
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Mortality Salience and Social Dominance Orientation on Attitudes Toward Illegal Immigrants

Abstract: The paper examines the hypothesis that the effects of mortality salience on attitudes toward illegal immigrants are moderated by individual differences predisposing participants toward prejudice or intolerance. A total of 122 university students completed measures of political orientation, authoritarianism, and social dominance orientation prior to being randomly assigned to a mortality salience or control condition. Political conservatism, authoritarianism, and social dominance orientation were all associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 18 publications
0
13
0
5
Order By: Relevance
“…Results of research also revealed a negative relation between authoritarianism and attitudes toward others (Fisher, Deason, Borgida, & Oyamot, 2011;Oyamot, Borgida, & Fisher, 2006). In addition, studies indicated that raters who were high in social dominance orientation, political conservatism, and authoritarianism were more likely to view immigrants negatively than their counterparts (Bassett, 2010). Finally, other researchers (Guimond, Olveria, Kamiesjki, & Sidanius, 2010) showed that individuals in France who were high in inequality and social dominance orientation were more prejudiced regarding immigrants than those low in inequality and social dominance.…”
Section: Authoritarianism and Social Dominancementioning
confidence: 95%
“…Results of research also revealed a negative relation between authoritarianism and attitudes toward others (Fisher, Deason, Borgida, & Oyamot, 2011;Oyamot, Borgida, & Fisher, 2006). In addition, studies indicated that raters who were high in social dominance orientation, political conservatism, and authoritarianism were more likely to view immigrants negatively than their counterparts (Bassett, 2010). Finally, other researchers (Guimond, Olveria, Kamiesjki, & Sidanius, 2010) showed that individuals in France who were high in inequality and social dominance orientation were more prejudiced regarding immigrants than those low in inequality and social dominance.…”
Section: Authoritarianism and Social Dominancementioning
confidence: 95%
“…In examining the interplay between social dominance orientation and mortality salience, Bassett (2010) found that participants who were high in social dominance were more negative toward illegal immigrants in a mortality salience condition, but not in a control condition. There was no main effect for mortality salience on attitudes toward illegal immigrants in Bassett's findings, only an interaction between social dominance orientation and mortality salience on attitudes.…”
Section: Social Dominance Orientationmentioning
confidence: 99%
“…Es así que si bien el recordar a las personas su carácter mortal llevó a los sujetos de algunos estudios a rechazar a aquellos percibidos como distintos o a evitar miembros de exogrupos, esto ocurre solo en quienes puntúan alto en la escala de Autoritarismo de Ala Derecha (Greenberg et al, 1990). Por el contrario, quienes presentan puntuaciones bajas en esta escala, mantuvieron, tras la saliencia de la mortalidad, sus actitudes previas hacia el exogrupo en algunos estudios (Basset, 2010) e incluso manifestaron actitudes más favorables hacia el exogrupo en otros (Weise, Arciszewski, Verlhiac, Pyszczynski y Greenberg, 2012). Así, se ha encontrado que la saliencia de la mortalidad conduce a un incremento del favoritismo endogrupal, a buscar mayores niveles de distintividad óptima y a ceñirse a las normas y estándares que protegen la visión cultural del mundo de un individuo (Arndt et al, 2002).…”
Section: Saliencia De La Mortalidad Y Construcción De La Amenazaunclassified